2004
DOI: 10.2134/jeq2004.1331
|View full text |Cite
|
Sign up to set email alerts
|

Sorption of Sulfonamide Pharmaceutical Antibiotics on Whole Soils and Particle‐Size Fractions

Abstract: Residues of pharmaceutical antibiotics are found in the environment, whose fate and effects are governed by sorption. Thus, the extent and mechanisms of the soil sorption of p-aminobenzoic acid and five sulfonamide antibiotics (sulfanilamide, sulfadimidine, sulfadiazine, sulfadimethoxine, and sulfapyridine) were investigated using topsoils of fertilized and unfertilized Chernozem and their organic-mineral particle-size fractions. Freundlich adsorption coefficients (K(f)) ranged from 0.5 to 6.5. Adsorption incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
188
2
10

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 369 publications
(222 citation statements)
references
References 45 publications
22
188
2
10
Order By: Relevance
“…Available data show that antibiotic consumption for veterinary purposes is more than several kilotons per year in America, Europe, and China, and tetracyclines (TCs) and sulfonamides (SMs) are two kinds of the most widely used antimicrobial agents in animal feeding (Arikan et al 2009;Sarmah et al 2006;Shen et al 2009). Antibiotics are designed to be easily excreted by the acceptors after administration (Halling-Sørensen et al 2002;Thiele-Bruhn et al 2004), which results in high antibiotic residues in animal manure. Some reported antibiotic concentrations in manures reach the level of microgram per kilogram (Haller et al 2002;Hamscher et al 2002;Martínez-Carballo et al 2007;Zhao et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Available data show that antibiotic consumption for veterinary purposes is more than several kilotons per year in America, Europe, and China, and tetracyclines (TCs) and sulfonamides (SMs) are two kinds of the most widely used antimicrobial agents in animal feeding (Arikan et al 2009;Sarmah et al 2006;Shen et al 2009). Antibiotics are designed to be easily excreted by the acceptors after administration (Halling-Sørensen et al 2002;Thiele-Bruhn et al 2004), which results in high antibiotic residues in animal manure. Some reported antibiotic concentrations in manures reach the level of microgram per kilogram (Haller et al 2002;Hamscher et al 2002;Martínez-Carballo et al 2007;Zhao et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This suggested that except for hydrophobic partitioning, pore-filling and/or some specific interactions with functional groups of soil organic matter and clay minerals were involved in adsorption (Thiele-Bruhn et al, 2004). Compared to the adsorption on soil, it is clearly shown that adsorption of STZ on peat was markedly stronger due to higher organic content in peat ( Fig.…”
Section: Adsorption Isothermsmentioning
confidence: 96%
“…1a and b). Previous studies reported that sulfonamide antibiotics were preferred to be adsorbed to soil organic matter through site-specific hydrogen bonds and van der Waals interactions (Thiele-Bruhn et al, 2004;Kahle and Stamm, 2007). The adsorption isotherms of T on peat and soil are also nonlinear, with n values 0.52 and 0.58, indicating that some specific interactions were involved in adsorption.…”
Section: Adsorption Isothermsmentioning
confidence: 98%
“…57 Em decorrência de baixos valores de K d e da formação de interações mais fracas com o solo (como interações de van der Waals e ligações de hidrogênio), fármacos como as sulfonamidas (SF) apresentam alta mobilidade no meio ambiente. 15,19,68,72 Deste modo, estes compostos podem ser facilmente lixiviados alcançando águas superficiais e lençóis freáticos e, consequentemente, contaminar a água potável. 13,25 Até o presente momento, poucos trabalhos foram realizados com o intuito de elucidar os mecanismos envolvidos na sorção de antimicrobianos em solos.…”
Section: +unclassified
“…74,75 De acordo com a OECD 106, o coeficiente de sorção de contaminantes é determinado por meio da adição de uma alíquota com volume e concentração conhecidas do composto de interesse às amostras de solos inicialmente secas, pesadas e pré-equilibradas com CaCl 2 0,01 mol L O ajuste ao modelo de Freundlich foi satisfatoriamente obtido em diversos estudos de sorção de antimicrobianos em solos, 56,58,65,67,68 apresentando melhor coeficiente de correlação (r) quando comparado ao modelo de sorção de Langmuir. 64,69 Entretanto, em outras situações, o modelo de Langmuir (Equação 3) mostrou-se mais adequado.…”
Section: Determinação Dos Coeficientes De Sorção E Dessorção De Contaunclassified